A epistemologia do princípio do livre convencimento: reminiscência de um paradigma autoritário de processo no âmbito do novo código de processo civil - Wild, Rodolfo (Universidade do Vale do Rio dos Sinos, 2016)
The purpose of this study is to demonstrate the “status quo” of Brazilian judicial decision´ formation in regard to the “rational persuasion model” in the judicial decision-making process, especially in light of the signs of its maintenance, even under the New Civil Procedure Code of 2015. Based on this, the research intends to show how the use of the “rational persuasion model” in the judicial decision-making process has contributed to the exacerbation of judicial discretion on such decisions, through the selection of material evidence with a view to conferring a layer of apparent rationality in said decisions. In this context, it also intends to demonstrate how this conception or technique is the result of an authoritarian paradigm of process, introduced in Brazil with the 1939 Civil Procedure Code, based mainly on the influences of the work of scholars as Giuseppe Chiovenda. Furthermore, as the maintenance of this paradigm was facilitated, on one hand, by the continuity of certain conceptions of legal positivism, differentiating, for that, normativist positivism inspired by the work of Hans Kelsen of the one who preceded him, that is, legalistic or exegetical theory. On the other hand, it was also facilitated by a mistaken understanding of the rational persuasion model as a procedural principle to be applied in the judicial decision-making process. Thus, the study investigates both, the object of the process and the object of the debate, focusing in its different doctrinal approaches to demonstrate that, in the general theory of the judicial process, rational persuasion model does not find a place as a specific part in any of the studied objects. From this model or principle arises the imprecision - and even lack of doctrinal rigor - about the legal nature of “rational persuasion model”, which is helping to continue to elude both the theoretical and the practical problems related to the motivation of judicial decisions. All this complex set of factors, in short, has contributed to the fact that the judicial decision-making process and developing precedents continues to repeat, at the present time, the lessons of Chiovenda, inspired by an authoritarian paradigm, with respect to applying a rational persuasion model and enhancing judicial discretion in the decision-making process.
Keywords: Livre convencimento; Princípio da autoridade no processo civil; Positivismo; Objeto do processo; Objeto do debate; Rational persuasion model; Authoritarian paradigm of process; Positivism; Object of the process; Object of the debate; ACCNPQ::Ciências Sociais Aplicadas::Direito